Analysis of Hotspot Network Security Using the OpenSSL (Secure Socket Layer) Security Method at the PTPN 7 Musi Landas Plantation Office - Al Harits Athif (Jurnal Jaringan Komputer dan Keamanan, 2025)
For wireless network security on access point devices, the security method often used is the WEP/WPA/WPA2 method. Almost all wireless network users, on average, implement their access point devices using this method. This method is well known for its ability to secure wireless network security. However, the WEP/WPA/WPA2 method can still be penetrated by hacking software using the brute-force attack and dictionary methods. This hacking software is widely available on the internet. The next weakness is that this method only uses a password when connecting to the access point device. Consequently, the password can easily spread if one user gives their password to another user, and it is easily known by other users, and so on. The SSL (Secure Socket Layer) method has been widely used for securing websites that require a high level of security, such as banking websites, hosting, online buying and selling, and so forth, which usually use the HTTPS (Hyper Text Transfer Protocol Secure) protocol. Implementation of a gateway server functions as an internet router on both wired and wireless networks. This is a solution that can help communication between computers and a hotspot internet security system. Users will first log in by entering a user name and password when accessing the internet using the Secure Socket Layer (SSL) security method.